2010
DOI: 10.2165/11535990-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Prevent Cellular Rejection in Pediatric Heart Transplant Recipients

Abstract: Despite more than 40 years' experience in pediatric heart transplantation, cellular rejection remains a significant cause of morbidity and mortality. In this review, strategies and agents to prevent acute cellular rejection are discussed. Strategies to prevent rejection are divided into two phases - induction and maintenance therapies. Currently, the most commonly used induction agents are polyclonal antibodies (rabbit or equine antithymocyte globulin) and interleukin-2 receptor antibodies (daclizumab or basil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…While early withdrawal of steroids is a well established strategy in pediatric transplant recipients, there is only limited experience with-reduced-CNI or CNI-free regimens [33, 34]. Everolimus is not currently licensed in children and its use in pediatric heart transplant patients is largely restricted to high-volume centers [35]. There are no randomized trials.…”
Section: Everolimus In Heart Transplant Recipients: the Key Studiesmentioning
confidence: 99%
“…While early withdrawal of steroids is a well established strategy in pediatric transplant recipients, there is only limited experience with-reduced-CNI or CNI-free regimens [33, 34]. Everolimus is not currently licensed in children and its use in pediatric heart transplant patients is largely restricted to high-volume centers [35]. There are no randomized trials.…”
Section: Everolimus In Heart Transplant Recipients: the Key Studiesmentioning
confidence: 99%
“…However, they are associated with many adverse effects, especially in the pediatric population. 21,22 Prednisone use in children is decreasing with ISHLT registry data revealing that 66% of recipients were discharged on prednisone in the most recent era (January 2010-June 2018) compared to 74% in the previous era (January 2005-December 2009). 23 Multiple registry analyses have reported that corticosteroids can be avoided in children with excellent freedom from rejection and overall post-transplant survival outcomes.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…MMF is an anti‐proliferative agent and an antimetabolite that interrupts purine metabolism in T and B lymphocytes 60 . It is used as an adjunctive agent to CNI and has largely replaced the use of azathioprine.…”
Section: Management Of Cavmentioning
confidence: 99%
“…PSI, otherwise known as mTOR inhibitors, are used for the prevention of both acute and chronic rejection. Sirolimus is a macrolide antibiotic with a structure similar to that of tacrolimus, and everolimus is an analog of sirolimus that differs by one hydroxyl group 60 . With the arrival of PSIs there has been multiple studies assessing whether this class of drugs offer further advantages in preventing and treating CAV; however, multiple adult studies have shown mixed results.…”
Section: Management Of Cavmentioning
confidence: 99%
See 1 more Smart Citation